2011
DOI: 10.3727/096368910x552844
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Expressed Genes Identified in the CD4+ T Cells of Allograft Rejection Mice

Abstract: Allograft rejection is a leading cause for the failure of allotransplantation. CD4+ T cells play critical roles in this process. The identification of genes that alternatively expressed in CD4 + T cells during allograft rejection will provide critical information for studying the mechanism of allograft rejection, finding specific gene markers for monitoring, predicting allograft rejection, and opening new ways to regulate and prevent allograft rejection. Here, we established allograft and isograft transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 70 publications
(111 reference statements)
0
18
0
Order By: Relevance
“…2B). Xu et al (10) recently reported a gene expression profile comparison after isoskin or alloskin grafting into severe combined immunodeficient mice with homologous T-cell transfer as a means to obtain a genome-wide view for candidate genes in CD4 + T cells related to allotransplantation. The data in our study compared intragraft mRNA profiles in grafts transplanted into primary or secondary recipients and highlight a role for genes associated with Tregs, already implicated in the acceptance of primary grafts under cover of CD200 overexpression (6), in the maintenance of graft survival, and immunomodulation, in secondary recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Xu et al (10) recently reported a gene expression profile comparison after isoskin or alloskin grafting into severe combined immunodeficient mice with homologous T-cell transfer as a means to obtain a genome-wide view for candidate genes in CD4 + T cells related to allotransplantation. The data in our study compared intragraft mRNA profiles in grafts transplanted into primary or secondary recipients and highlight a role for genes associated with Tregs, already implicated in the acceptance of primary grafts under cover of CD200 overexpression (6), in the maintenance of graft survival, and immunomodulation, in secondary recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In all our studies of CD200-mediated immunoregulation, we have explored immunity and gene expression profiles in primary recipients where the CD200/CD200R immunoregulatory axis was perturbed. Other groups have similarly focused on characterization of the gene expression profile in primary graft recipients (9,10). Increased attention is now directed at mechanism(s) responsible for ongoing attenuation of rejection.…”
mentioning
confidence: 97%
“…Our previous study indicated that IL-27Rα was up-regulated in CD4 + T cells in acute allorejection [16]. Meanwhile, we also demonstrated that increased IL-27Rα expression promoted alloreactive spleen cell proliferation.…”
Section: Introductionmentioning
confidence: 61%
“…Our previous study proved that IL-27Rα was up-regulated in CD4 + T cell-mediated allorejection. Data reported that CD4 + T cells and macrophages could directly result in allogeneic graft rejection [10,16,40,41]. Considering that allogeneic grafts have severe inflammatory infiltration, such as CD4 + T cells and macrophages, we postulated that IL-27Rα may act as a targeted biomarker to monitor acute allogeneic graft rejection, based on graft inflammatory cell infiltration, non-invasively and visually.…”
Section: Discussionmentioning
confidence: 98%
“…22 Furthermore, in our previous study, an approximately fivefold overexpression of the pim2 gene, as determined by sequencing-based serial analysis of gene expression, was detected in the allograft-activated CD4 1 T cells, which suggests a potential role of the Pim2 kinase in allograft rejection. 23 Considering all of the aforementioned results, we hypothesize that the Pim2 kinase may participate in allograft rejection through targeting the apoptosis of CD4…”
Section: Cd4mentioning
confidence: 99%